(NsTIHOTWORENIQ(B: [1908-1925]; s (NnOWYE STIHI(B: [1930-1937] / s (N~ASTX (B1s - (NmANDELX[TAM(B, (NoSIPs ((NmOSKWA(B: s (NhUDOVESTWENNAQ LITERATURA(B, s, 1990)
(NpERWYJ TOM sO^INENIJ KRUPNEJ[EGO RUSSKOGO PO\TA (BXX (NWEKA o(B. (N|(B. (NmANDELX[TAMA (B(1891-1938) (NSOSTAWILI STIHOTWORENIQ(B, (NSOZDANNYE IM NA PROTQVENII VIZNI(B, (NWKL@^AQ STIHI DLQ DETEJ(B.s
rus
Keywords: (NsTIHOTWORENIQs